A comparative study between traditional and sports school uniforms on cardiorespiratory and muscular fitness and waist-height-to-ratio in adolescents - Cristi-Montero, Carlos; Martínez-Flores, Ricardo; Porras, Felipe; Sadarangani, Kabir P.; Ferrari, Gerson; Aguilar-Farias, Nicolas; Silva, Inacio Crochemore M.; Reyes-Amigo, Tomas; Rodriguez-Rodriguez, Fernando (Frontiers in Public Health, 2023)
Background: Improving health of children and adolescents is crucial for their overall development. Therefore, it is essential to explore factors that may influence their health at both the public health and school system levels. Objective: This study compares physical fitness components and waist-height-to-ratio (WHtR) in adolescents according to school uniforms, namely the traditional uniform (i.e., shirt and school necktie in boys and skirt and blouse in girls) and the sports uniform (i.e., polo shirts or t-shirts and sport or short trousers). Additionally, it seeks to investigate potential differences in these measures based on sex and school type (i.e., public, subsidized, and private). Methods: This cross-sectional study used data from the Chilean national learning outcome assessment system (SIMCE) -2014 and involved 8,030 adolescents. Cardiorespiratory fitness (CRF) and muscular fitness (MF) were measured. WHtR was assessed as a health cardiovascular indicator. Mixed models and ANCOVA were performed to compare uniform types, adjusting for multiple covariates. P-value and effect size (ES) was used to establish significant results. Results: Overall, sports uniforms (SU) were linked to higher CRF (p < 0.001) than the traditional uniform (TU). Boys from private schools wearing SU presented higher CRF (p = 0.016; ES = 0.37), and a positive trend was observed for MF (p = 0.645; ES = 0.21). In subsidized, a trend was found in CRF (p = 0.005; ES = 0.16). Girls wearing SU from private schools showed a positive trend in CRF (p = 0.167; ES = 0.28). Trends in WHtR were found in both sexes from private (p = 0.555; ES = 0.24; p = 0.444; ES = 0.25, respectively). Conclusion: Wearing SU seems a promissory alternative to promote healthy physical fitness and body composition at the educational level. However, the relationship between higher physical activity and CRF, MF, and lower WHtR due to SU must be verified. Finally, when deciding to implement this measure, special attention must be paid to boys from public schools and girls from all types of schools.